Creative Process and Transformative Dance in Brazil. (2014) - Vieira, Alba Pedreira
Abstract : This paper explores dance issues focusing on the creative process as it relates to transformative dance, embodiment, and power relations from an embodied perspective. I will illustrate the complexity of the Brazilian dance context in relation to similar as well as diverse aspects in a globalized society. The focus is on transformative dance as intimately related to values from an embodied perspective that defies contemporary thoughts on power relations between choreographers and dancers. This way of thinking and acting poses implications and challenges that might lead toward transformative dance through new ways of approaching self, world, body, power, and knowledge. Emphasizing the multiple dimensions of dance composition and research on dance in Brazil, the presentation is also intended to enrich, exchange, and mutually comment on ideas and issues raised.